The protective effect of Phyllanthus emblica Linn. extract against doxorubicin-induced hepatotoxicity in rats - Eka Susilawati; I Nyoman Ehrich Lister; Edy Fachrial (Universitas Ahmad Dahlan, 2021)
Recently many researches have been carried out on Malacca fruit extract and its potential protective effect on in vivo organ toxicity. However, there is still no research on the protective effect of Malacca (Phyllanthus emblica L.) fruit extract on induced hepatotoxicity of anticancer drugs, especially doxorubicin in rats. The objective of this study is to determine the potential protective effect of ethanol extract of Malacca fruit (P. emblica L.) against doxorubicin-induced hepatotoxicity in rats. A preliminary phytochemical test was done followed by administration extract into doxorubicin-induced rats. Histological studies were carried out to observe the effect of the extract on liver tissue. Phytochemical test results show that the ethanol extract of Malacca fruit contains flavonoids, phenols, tannins, triterpenoids, terpenoids, and alkaloids. The increasing value of ALT and ALP of doxorubicin-induced liver tissue proved the toxicity in liver tissue caused by doxorubicin. The ethanol extract of P. emblica L. at dosage 200 mg/kg BW and dosage 400 mg/kg BW on doxorubicin-induced rats were successfully played as an antioxidant to decrease the ALT and ALPvalues and improve liver tissue doxorubicin-induced by normal hepatocytes more dominant than lysis and less mark of bleeding and congestion of blood vessels.